E-safety in Web 2.0 learning environments: a research synthesis and implications for researchers and practitioners - Parmaxi, Antigoni; Papadamou, Kostantinos; Sirivianos, Michael; Stamatelatos, Makis (My University, 2017)
This study explores the research development pertaining to safety and security in Web 2.0 learning environments, as well as a review of web-based tools and applications that attempt to address security and privacy issues in Online Social Networks. Published research manuscripts related to safety and security in collaborative learning environments have been explored, and the research topics with which researchers and practitioners deal with are discussed, as well as implications for researchers and practitioners. This paper argues that Web 2.0 learning environments entail threats and challenges in the safety of both students and instructors, and further research needs to take place for handling and protecting the privacy of all involved stakeholders.
Keywords: Web 2.0; Social web; Social networking sites; Social media; Security; OSNs; Literature review; E-safety